2022
DOI: 10.3390/pathogens11101196
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Correlation of Virulent Salmonella Serovars (Extended Spectrum β-Lactamases) Isolated from Broiler Chickens and Human: A Public Health Concern

Abstract: This study aimed to detect the virulent Salmonella serovars (including ESBLs producing) isolated from broiler chickens and humans. Three hundred broilers and sixty human fecal samples were bacteriologically examined. Thirty (10%) and fourteen (23.4%) Salmonella isolates were recovered from broiler and human samples, respectively. The most predominant serovar was S. enteritidis and S. typhimurium. All Salmonella isolates were confirmed by conventional PCR-based invA and ompA genes. Multidrug resistant (MDR) iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The findings of the current study are similar to those reported by Ahmed et al [43], who obtained Salmonella by rate of 18.7 and 16.9%., respectively. Meanwhile, our findings were unlike those found by Orabi et al [44], who detected Salmonellae in a rate of 10.0%. Our observations propose the prospect that the environment has a potential role in circulating the pathogen between animals and human populations.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of the current study are similar to those reported by Ahmed et al [43], who obtained Salmonella by rate of 18.7 and 16.9%., respectively. Meanwhile, our findings were unlike those found by Orabi et al [44], who detected Salmonellae in a rate of 10.0%. Our observations propose the prospect that the environment has a potential role in circulating the pathogen between animals and human populations.…”
Section: Resultscontrasting
confidence: 99%
“…Furthermore, isolates obtained from cutting knives were considerably resistant to gentamycin (100.0%), followed by those obtained from intestinal swabs, hand swabs, and cutting boards at 93.3, 90.1%, and 8.9%, respectively. Similar findings were investigated by Doyle et al [55], Zishiri et al [56], Nabil and Younis [57] and Orabi et al [44]. Notably, the exuding rates of microbial resistance to most of the investigated antibiotics in this study were not surprising, which suggests the abuse and/or overuse of most common therapeutic antimicrobial classes utilized in the field of the poultry industry with risk of transmission of this resistance to human traits through the food chain [58,59].…”
Section: Resultssupporting
confidence: 88%
“…Many authors in previous studies agree with us in the opinion that the most common serotypes of salmonella in humans and animals were S. typhimurium and S. enteritidis [ 15 , 18 20 ]. However, a previous study in Ethiopia demonstrated that the most common serovar were S. dublin and S. Virchow [ 21 ].…”
Section: Discussionsupporting
confidence: 56%
“…Antibiotics used in this study were streptomycin (30 μg), ciprofoxacin (5 μg), nalidixic acid (30 μg), gentamicin (10 μg), and kanamycin (30 μg). Resistance to two or more antimicrobials of diferent classes was considered to be multidrug-resistant (MDR) [26].…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%